The effect of priming with gibberellic acid on improving the germination of seeds obtained from self-pollinated of different varieties of Petunia hybrida - Leyla Cheheltanan; Ali Tehranifar; Mahmoud Shoor; Seyyed Hossein Neamati; Saeed Khosravi (علوم و فناوری بذر ایران, 2025)
Self-pollination induces a phenomenon known as inbreeding depression in heterozygous plants, which in turn leads to a reduction in seed germination and seedling growth. On the other hand, seed priming with plant hormones such as gibberellic acid is a technical approach that potentially results in the improves of rapid and continuous seed germination and subsequent plant growth. Therefore, this research aimed to investigate the effect of different concentrations of gibberellic acid on the improvement of seed germination resulting from self-pollination in various varieties of Petunia hybrida in a factorial experiment with three replications as a completely randomized design. The treatments consisted of four levels of gibberellic acid (0, 50, 100, and 150 mg/L) and seeds obtained from self-pollination of Iranian Petunia, Tango Blue, Tritunia Pink Morn, and Tritunia White. The results indicated that seed priming with gibberellic acid, especially at a concentration of 100 mg/L, led to a significant increase in the activity of α-amylase and β-amylase by 6.56% and 1.57%, respectively. This increase resulted in 8.54% rise in soluble sugars content, providing energy that significantly enhanced germination percentage, germination speed, average time required for germination, seed vigor index, germination energy, and the fresh and dry weight of plumule and radicle. Moreover, among different varieties, seeds obtained from self-pollination of Iranian petunia demonstrated a higher germination percentage and germination speed compared to seeds from other varieties, indicating a superior capability in maintaining vigor potential, germination percentage, and germination speed.